(untitled) (Praxis Educativa, 2013)
Each time people speak about education quality, good or bad quality, confrontations arise because everyone expresses what he/she thinks, loaded with ideology and therefore, subjectivity. It depends on the circumstance in which we are asked the question as well as on the parameters and the paradigms the evaluator supports. In this paper it is considered that the quality of education is sieved by three main paradigms: the necessity of reading, the teacher’s passion showing his/her strong convictions on their role, and fulfilling three essential requirements: to plan, to develop and to evaluate the class. This task requires the capacity of correction, reflection and study, and that the teachers dare to create work ways that put themin the place of others.